Predictors of reliable symptom change: Secondary analysis of the Preschool Autism Communication Trial. (March 2018) - Hudry, Kristelle; McConachie, Helen; Le Couteur, Ann; Howlin, Patricia; Barrett, Barbara; Slonims, Vicky; ,
Background and aims: Despite recent gains in the amount and quality of early autism intervention research, identifying what works for whom remains an ongoing challenge. Exploiting data from the Preschool Autism Communication Trial (PACT), we undertook secondary analysis to explore prognostic indicators and predictors of response to one year of PACT therapy versus treatment as usual within this large and rigorously characterised cohort recruited across three UK trial sites. Methods: In this secondary analysis of variability in child gains on the primary trial outcome measure – social-communication symptom severity – we used a pragmatic and data-driven approach to identify a subgroup of children who showed reliable improvement and a subgroup showing clear lack thereof. We then tested which among several baseline child and family factors – including measures routinely collected in research trials and clinical practice – varied as a function of child outcome status and treatment group. Results: Greater baseline child non-verbal ability was a significant prognostic indicator of symptom reduction over time (i.e. irrespective of treatment group). By contrast, parent synchrony presented as marginal predictor, and trial recruitment site as a significant predictor, of differential outcome by treatment group. Specifically, lower parent synchrony showed some association with poorer outcomes for children from families assigned to treatment as usual (but with no such effect for those assigned to PACT). Similarly, children at one recruitment site were more likely to have poorer outcomes if assigned to treatment as usual, compared to children at the same site assigned to PACT. Conclusions: The current data contribute to an evidence base indicting that early non-verbal ability is a robust indicator of generally better prognosis for young children with autism. Lower parent synchrony and a broadly more deprived socio-geographical context may inform the appropriate targeting of PACT. That is, given that the former factors predicted poorer outcome in children from families assigned to treatment as usual, the receipt of a relatively low-dose, parent-mediated and communication-focused therapy might be developmentally protective for young children with autism. Nevertheless, results from this study also highlight the paucity of meaningful predictors of outcome among routine clinical characterisation measures such as those investigated here. Implications: Understanding the factors associated with differential treatment outcomes is critical if we are to individualise treatment decisions for children with autism. Inherently tied to this objective is a need to delineate those factors which specifically predict positive response (or lack of response) to one or other treatment option, versus those that indicate generally better (or poorer) prognosis, irrespective of treatment.